9(12/7)+7=

Simple and best practice solution for 9(12/7)+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(12/7)+7= equation:


9(12/7)+7=0

We simplify the equation to the form, which is simple to understand
9(12/7)+7=0

Reorder the terms in parentheses
+(+15.428571428571)+7=0

Remove unnecessary parentheses
+15.428571428571+7=0

We move all terms containing to the left and all other terms to the right.
0=0-15.428571428571-7

We simplify left and right side of the equation.
0=-22.428571428571

0=-22.428571428571

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| .55=log(x) | | 3x-6x+6=x-5+11 | | -4m-7(6m-4)= | | (7x-4)/5=0 | | 2(12/7)-5= | | -5y^2+8y-3=0 | | 16z+5z=-3 | | 10+11(x)=87 | | 3k^2-9k+5=0 | | (w/5)=20 | | 7z-(2z-8)=-2 | | (X/-2)=(-9) | | (2x-5)=(9x+7) | | 6(1-1x)=11x-2(1x+2) | | 3v^2-8v-5=0 | | (x+1)(x+1)=(x+1)(x+1) | | -3=x/3 | | 7-3x=173 | | (6x-4)-8=12 | | -3=-4+5a-4a | | 7t^2-5t-6=0 | | 16x+3=9x+73 | | -5*a+(-5*b)=5 | | -5/8x=-60 | | ((m^(1/5))/((m^(4/5))(m^-(4)))=m^(a/b) | | 8d^2+6d+1=0 | | 5(.5-3)+3(.5+3)=2(.5)-3 | | 8u^2-9u-3=0 | | 3x^3+33x^2+90x= | | 2m^2+4m+2=0 | | 3x^3+6x=4x^2+8 | | x+2x+2= |

Equations solver categories